Solar Energy Resource Use as An Alternative Energy in The Electric Household Banda Aceh - Sarini Vita Dewi (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
Aceh is one area in Indonesia which has the best sunshine throughout his season. Banda Aceh region of Indonesia, especially in continual sunlight for 11-13 hours a day. From these facts, Banda Aceh is an area with the potential to make solar electricity as an energy source. From the research that has been previously applied solar energy is an energy efficient and economical and reliable environment because solar energy is harnessed as a clean electrical energy with no pollution, easy to transport, close to the center so that the burden of the energy distribution is very simple. This research aims to develop technological innovations sourced electricity generation from solar energy. Converting solar energy into electricity using Photovoltaic working principles. While the electrical energy generated is stored in a battery. The benefits of research to empower optimal solar energy as a source of electrical energy.Keyword: sun, electricity, alternative, energy